A new Cosmocercoides species (Ascaridida: Cosmocercidae), C. wuyiensis n. sp., from the Asiatic frog Amolops wuyiensis (Amphibia: Anura). (2020) - Liu, Y.; Yu, Q.; Shu, Y.-L.; Zhao, J.-H.; Fang, J.-Y.; Wu, H.-L.
Abstract: We identified and characterized a new cosmocercid nematode species, Cosmocercoides wuyiensis n. sp., through microscopic examination and sequencing of the partial small ribosomal RNA gene (18S rDNA), internal transcribed spacer (ITS) and mitochondrial cytochrome c oxidase subunit 1 (COI) genes. The new species was isolated from the intestine of the Asiatic frog Amolops wuyiensis Liu and Hu, 1975 captured from four localities of the Anhui province in south-east China. Among the 25 recorded species of the Cosmocercoides genus, the morphology of C. wuyiensis n. sp. is closest to that of C. kiliwai and C. malayensis, which were isolated from various Mexican frog and Malaysian lizard species, respectively. However, C. wuyiensis n. sp. displayed several distinguishing features, such as small size of the male body, two spicules of unequal lengths in the male, small gubernaculum, pre-, ad- and post-cloacal caudal rosette papillae in the ratio of 18–24:2:6 and simple papillae in the ratio of 14:multiple:4, circle and number of punctation in each rosette at 1:11–16, sharply conical tail-end and the presence of lateral alae and somatic papillae in both sexes. BLAST and the phylogenetic analyses of the 18S rDNA and ITS sequences indicated that C. wuyiensis n. sp. belonged to the genus Cosmocercoides, while that of the COI gene sequence of C. wuyiensis n. sp. showed 16.36% nucleotide divergence with C. pulcher and 47.99% nucleotide divergence with C. qingtianensis. The morphological and molecular characterization of C. wuyiensis n. sp. provides new taxonomic data for this genus.